Suppression of Arrhythmia by Enhancing Mitochondrial Ca2+ Uptake in Catecholaminergic Ventricular Tachycardia Models - Schweitzer, Maria K.; Wilting, Fabiola; Sedej, Simon; Dreizehnter, Lisa; Dupper, Nathan J.; Tian, Qinghai; Moretti, Alessandra; My, Ilaria; Kwon, Ohyun; Priori, Silvia G.; Laugwitz, Karl Ludwig; Storch, Ursula; et al. (JACC: Basic To Translational Science, 2017)
Cardiovascular disease-related deaths frequently arise from arrhythmias, but treatment options are limited due to perilous side effects of commonly used antiarrhythmic drugs. Cardiac rhythmicity strongly depends on cardiomyocyte Ca2+ handling and prevalent cardiac diseases are causally associated with perturbations in intracellular Ca2+ handling. Therefore, intracellular Ca2+ transporters are lead candidate structures for novel and safer antiarrhythmic therapies. Mitochondria and mitochondrial Ca2+ transport proteins are important regulators of cardiac Ca2+ handling. Here, the authors evaluated the potential of pharmacological activation of mitochondrial Ca2+ uptake for the treatment of cardiac arrhythmia. To this aim, the authors tested substances that enhance mitochondrial Ca2+ uptake for their ability to suppress arrhythmia in a murine model for ryanodine receptor 2 (RyR2)-mediated catecholaminergic polymorphic ventricular tachycardia (CPVT) in vitro and in vivo and in induced pluripotent stem cell-derived cardiomyocytes from a CPVT patient. In freshly isolated cardiomyocytes of RyR2R4496C/WT mice efsevin, a synthetic agonist of the voltage-dependent anion channel 2 (VDAC2) in the outer mitochondrial membrane, prevented the formation of diastolic Ca2+ waves and spontaneous action potentials. The antiarrhythmic effect of efsevin was abolished by blockade of the mitochondrial Ca2+ uniporter (MCU), but could be reproduced using the natural MCU activator kaempferol. Both mitochondrial Ca2+ uptake enhancers (MiCUps), efsevin and kaempferol, significantly reduced episodes of stress-induced ventricular tachycardia in RyR2R4496C/WT mice in vivo and abolished diastolic, arrhythmogenic Ca2+ events in human iPSC-derived cardiomyocytes. These results highlight an immediate potential of enhanced mitochondrial Ca2+ uptake to suppress arrhythmogenic events in experimental models of CPVT and establish MiCUps as promising pharmacological tools for the treatment and prevention of Ca2+-triggered arrhythmias such as CPVT.
CRIS-Team Scopus Importer:2023-03-08
Keywords: CPVT; MCU; MiCUp; mitochondria; RyR2; VDAC2